Isolation of Bacterial Uropathogens and Their Antibiotic Susceptibility Pattern in Brahmanbaria Medical College (Journal of Brahmanbaria Medical College, 2026)
Background: Urinary Tract Infections (UTIs) are the most common bacterial infections in developing countries. Area-specific monitoring studies aim to comprehend the pathogen types and resistance patterns of urinary tract infections. The study aims to identify the type and pattern of antibiotic resistance in uropathogens from patients at Brahmanbaria Medical College Hospital. Materials and methods: A hospital-based cross-sectional study was conducted from January to December 2023. Urine samples were collected using the mid-stream “clean catch” method from 5000 clinically suspected cases of urinary tract infections and tested bacteriologically using standard procedures. According to Clinical and Laboratory Standards Institute guidelines, an antimicrobial susceptibility test was performed for the isolated pathogens using the Kirby-Bauer disk diffusion method. Results: A significant amount of uropathogens were detected in 50.9% of the total patients. UTIs were more common in females, and young people were more affected by uropathogens. The most common uropathogens isolated were Escherichia coli (E.coli) 1780 (69.94%), and Staphylococcus saprophyticus 326(12.81%). Very high frequencies of resistance have been ranging from 70-100 % to cefixime, cefuroxime, cotrimoxazole, azithromycin, and moderately high resistance to ceftriaxone, ciprofloxacin, and amoxiclav. Staphylococcus saprophyticus and Enterococcus spp showed moderate sensitivity to linezolid but Gram-negative uropathogen showed high resistance to linezolid. Amikacin, gentamicin, meropenem, nitrofurantoin, and piperacillin-tazobactam showed good sensitivity patterns against E. coli, Enterobacter spp, Pseudomonas spp, Proteus spp, Klebsiella spp, Enterococcus spp, Staphylococcus saprophyticus. Conclusion: The study revealed E. coli isolates as the primary pathogens, causing high resistance to commonly prescribed drugs. Antibiotics became limited treatment options for UTIs. It is now essential to conduct routine, frequent studies and surveillance.JBRMC, Volume 08 Issue 01 January 2026 ; 15-19